Benchmarking Wearable Robots: Challenges and Recommendations From Functional, User Experience, and Methodological Perspectives - Torricelli, Diego; Rodriguez-Guerrero, Carlos; Veneman, Jan F.; Crea, Simona; Briem, Kristin; Lenggenhager, Bigna; Beckerle, Philipp (Frontiers in Robotics and AI, 2020)
Wearable robots (WRs) are increasingly moving out of the labs towards real-world applications. In order for WRs to be effectively and widely adopted by end-users, a common benchmarking framework needs to be established. In this article, we outline the perspectives that in our opinion are the main determinants of this endeavour, and exemplify the complex landscape into three areas. The first perspective is related to quantifying the technical performance of the device and the physical impact of the device on the user. The second one refers to the understanding of the user’s perceptual, emotional, and cognitive experience of (and with) the technology. The third one proposes a strategic path for a global benchmarking methodology, composed by reproducible experimental procedures representing real-life conditions.. We hope that this paper can enable developers, researchers, clinicians and end-users to efficiently identify the most promising directions for validating their technology and drive future research efforts in the short and medium term.